Substituição lexical : o encapsulamento anafórico na construção do sentido em textos publicitários - Silva, Viviane Demetrio da (2013)
This research shows a study about the encapsulating anaphoric, assumed like cohesive resource of concised character, evaluative and of refferings recapture already presented in text effected by lexical replacement in publicity texts. There fore, the purpose of this research is to show that the construction of lexical meaning in publicity texts achieved throught the encapsulating anaphoric. The theoretical basis inspire itself in authors of textual linguistic, these authors study about referral anaphora: Apothéloz (2003); Bentes (2001); Cavalcante (2003); Cavalcante e Mesquita (2011); Koch (1997, 2002, 2003, 2004); Koch e Travaglia (1989); Koch e Marcuschi (1998); Koch, Morato e Bentes (2005); Koch e Elias (2006); Marcuschi (1998, 2001, 2002, 2005, 2007, 2008, 2012); Milner (2003); Mondada e Dubois (2003); Savioli e Fiorin (2007); Schimidt (1978); Van Dijk (1980) and, specially in Conte (2003) when he cites the linguistic phenomenon of anaphoric encapsulating. The methodological procedures are to identify the anaphoras to subsequently analyze the recapture inside the text, the research was accomplished in a descriptive and bibliographic form, since starting from the theoretical apparatus chosen, theoretical analysis was being woven in which was possible to identify the evaluative burden of lexical words used in the construction of meaning by anaphoric encapsulating